2020
DOI: 10.3390/ijerph17134627
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Measles Outbreak among Thai and Migrant Workers in Two Factories in Nakhon Pathom, Thailand, 2019

Abstract: On 22 March 2019 the Thai Department of Disease Control (DDC) was notified that 16 workers, including Thai and Myanmar migrant workers, from two factories located in Nakhon Phathom Province, had presented with a fever with rash during the previous 2 weeks. Active case finding was conducted among workers in both factories using face-to-face interviews. Suspected cases were defined as a worker who developed fever with rash with one of the following symptoms: cough, coryza or conjunctivitis. Testing for measles I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…( 10 ) Overcrowded environments and inadequate sanitation in Xaisomboun, as identified by the Lao People's Democratic Republic Social Indicator Survey, ( 3 ) also facilitate measles virus transmission. ( 16 ) The survey ( 3 ) also suggests that the community in Xaisomboun is hesitant to seek health care, as it reported that for children aged 0–59 months, advice or treatment was not sought for 48.4% of children with diarrhoea and 72% of those with fever compared with national rates of, respectively, 51% and 42%. ( 3 ) The unique languages and traditional beliefs of the Xaisomboun community may also play an important part in their health-seeking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…( 10 ) Overcrowded environments and inadequate sanitation in Xaisomboun, as identified by the Lao People's Democratic Republic Social Indicator Survey, ( 3 ) also facilitate measles virus transmission. ( 16 ) The survey ( 3 ) also suggests that the community in Xaisomboun is hesitant to seek health care, as it reported that for children aged 0–59 months, advice or treatment was not sought for 48.4% of children with diarrhoea and 72% of those with fever compared with national rates of, respectively, 51% and 42%. ( 3 ) The unique languages and traditional beliefs of the Xaisomboun community may also play an important part in their health-seeking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated economic contribution of immigrant workers was 4.3%−6.6% of Thailand's gross domestic product in 2010, while they represented 4.7% of the employed population ( 54 ). Vaccines covered by the National Immunization Programme should be available to all children regardless of nationality, as the cost of outbreak response and containment in the community is higher if they are not fully immunized ( 55 , 56 ). The MOPH should ensure funding to achieve this end.…”
Section: Thailand's Next Steps In Building Back Better Fairer and Mor...mentioning
confidence: 99%
“…Some communities house up to tens of thousands of workers with poor sanitation 14 and ventilation, 15 becoming epicentres for disease outbreaks. 16 In conjunction with living and work conditions, the low vaccination rates give rise to outbreaks such as measles in factory workers 17 and school children along borders. 18 Similarly, pulmonary tuberculosis (TB) is highly prevalent in migrant worker populations, but barriers in accessing care prevent them from getting proper treatment; illegal status and fear of arrest, 19 difficulty in transportation, financial restraints and lack of knowledge on where to seek treatment are all contributing factors 20 and migrant workers often end up self-medicating (this behaviour is not limited to TB).…”
Section: Migrant Workers: the Vulnerability Contextmentioning
confidence: 99%